I Ain't Gonna Let No One Disrespect Me: Does the Code of the Street Reduce or Increase Violent Victimization among African American Adolescents? - Stewart, Eric A. (Journal of research in crime and delinquency, 2006)
The authors extended Elijah Anderson's "code of the street" thesis to explain victimization among a longitudinal sample of 720 African American adolescents from 259 neighborhoods. Specifically, the authors assessed whether the street code promotes greater safety or aggravates the risk for victimization. Anderson portrayed the code of the street, which encourages individuals to appear aggressive and tough, as an adaptation necessary for safely functioning in a disadvantaged, high-crime community. He theorized that adopting the street code promotes respect among one's peers and would-be attackers, thereby increasing one's safety against victimization. The authors found no support for the idea that adopting the street code reduces victimization. Instead, their findings suggest that individuals who adopt the street code have higher levels of victimization. Furthermore, adopting the street code exacerbates the risk for victimization beyond what would be the case from living in a dangerous and disorganized neighborhood. [ABSTRACT FROM AUTHOR]